The Use of Social Networking Site to Increase Students’ Reading Achievement of State Junior High School 3 Of Rambang Niru: English - Repika Claudia Saputri; Mulyadi; Hanni Yukamana (Prodi Tadris Bahasa Inggris, 2024)
This study aims to describe how social networking site could improve students’ reading achievement of State Junior High School 3 of Rambang Niru. This research used the Classroom Action Research (CAR) which consists of four steps, namely planning, action, observation and reflection. Success Criteria of the Reasearch is the school minimal passing grade, which was 60. The result of this study is Social Networking Site can improve the students’ reading achievement of the eight gare students as Junior High School 3 of Rambang Niru. It could be seen in the result of cycle III. There were 28 students who had met English standard score was 60, it was around 87.5% and the mean students was 75.62. It is possible to draw the conclusion that social networking sites are highly beneficial and have a significant impact on raising students' reading achievement based on the findings in the previous chapter. Students can use social networking sites (SNS) to learn English outside of the classroom at any time and from any location, regardless of time or space constraints. Students utilized social networking sites (SNS) for studying, particularly English, as it was effective and adaptable.